Nanotechnology and COVID-19: Prevention, diagnosis, vaccine, and treatment strategies - Ayan, Sumeyra; Aranci-Ciftci, Kubra; Ciftci, Fatih; Ustundag, Cem B. (Frontiers in Materials, 2023)
In December 2019, Coronavirus pandemic (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) viruses, which affected the whole world, is emerged. The details on the epidemiology, infection source, transmission mode, and prognosis of SARS-CoV-2 gave in this review. Universal infection control standards such as hand hygiene, environmental cleanliness, use of personal protective equipment, and quarantine used to prevent the spread of COVID-19 without vaccine. However, many vaccine candidate studies carried out globally with using traditional and technological approaches. Innovations in technology allow the development of nanotechnological tools and the formation of systems that will inactivate SARS-CoV-2 in patients. It expected to include technologies that combine different disciplines, especially robotic applications, antimicrobial nanotechnology, and tissue engineering for the future treatment of COVID-19. This review-based work discusses the relationship of COVID-19 and nanotechnology based working principles.